2008
DOI: 10.1021/nl8029114
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Gold Nanoparticles Enable Molecular CT Imaging of Cancer

Abstract: X-ray based computed tomography (CT), is among the most convenient imaging/diagnostic tools in hospitals today in terms of availability, efficiency and cost. However, in contrast to magnetic resonance imaging (MRI) and various nuclear medicine imaging modalities, CT is not considered a molecular imaging modality since targeted and molecularly specific contrast agents have not yet been developed. Here we describe a targeted molecular imaging platform that enables, for the first time, cancer detection at the cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
565
2
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 723 publications
(570 citation statements)
references
References 31 publications
0
565
2
3
Order By: Relevance
“…Our extensive in vivo studies (in mice, pigs, and dogs) have confirmed that gold nanoparticles (AuNPs) show significantly higher x-ray absorption characteristics than iodinated CT agents (8,9,14,15). Recently, Kopelman and co-workers have demonstrated the feasibility of using targeted AuNPs embedded in cancer cells for CT imaging under in vitro conditions (16). Despite considerable progress achieved to date toward the development of target-specific AuNPs for use in early cancer detection, a vast majority of these systems perform well only under in vitro profiles and fail to maintain target specificity/efficacy under in vivo conditions (17).…”
mentioning
confidence: 76%
“…Our extensive in vivo studies (in mice, pigs, and dogs) have confirmed that gold nanoparticles (AuNPs) show significantly higher x-ray absorption characteristics than iodinated CT agents (8,9,14,15). Recently, Kopelman and co-workers have demonstrated the feasibility of using targeted AuNPs embedded in cancer cells for CT imaging under in vitro conditions (16). Despite considerable progress achieved to date toward the development of target-specific AuNPs for use in early cancer detection, a vast majority of these systems perform well only under in vitro profiles and fail to maintain target specificity/efficacy under in vivo conditions (17).…”
mentioning
confidence: 76%
“…Furthermore, NPs can be attached to antibodies to actively target key tumour characteristics in order to inform treatment options and prognosis (Popovtzer et al 2008, Jiao et al 2011.…”
mentioning
confidence: 99%
“…Macrophages are known as 'big eaters', that phagocytose nanomaterials like GNP with high rate [86]. The GNP have long been used in the detection and imaging of biological processes and diseases [46,47,61,62,70,87]. The broad range of GNP applications is based on their unique chemical and physical properties and, in particular, on their optical properties from the visible to the IR region, depending on the particle size, shape, and structure [88,89].…”
Section: Magnetic Particlesmentioning
confidence: 99%